2014
DOI: 10.1167/iovs.14-14704
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Multifocal Electroretinography and Optical Coherence Tomography in Eyes Undergoing Panretinal Photocoagulation for Diabetic Retinopathy

Abstract: A lower amplitude of mfERG and disrupted foveal ellipsoid zone status were significantly correlated with a worse visual prognosis in diabetic eyes after PRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The disruption of Müller cells in diabetic macular edema has also been shown in multifocal electroretinogram studies as a decrease of the P1 amplitude in the central ring produced by bipolar and Müller cells. 28,29 In particular, Esfahani et al reported that a decrease in P1 amplitude is associated with DRILs, IRC, and EZ disruption and also with visual acuity. 30 Further study on the relationship between foveal Müller cell cone disruption and multifocal electroretinogram will provide physiological evidence that the foveal Müller cell cone structure is a predictive biomarker.…”
Section: Post Hoc Studies Of Protocol T Evaluated the Effectiveness O...mentioning
confidence: 99%
“…The disruption of Müller cells in diabetic macular edema has also been shown in multifocal electroretinogram studies as a decrease of the P1 amplitude in the central ring produced by bipolar and Müller cells. 28,29 In particular, Esfahani et al reported that a decrease in P1 amplitude is associated with DRILs, IRC, and EZ disruption and also with visual acuity. 30 Further study on the relationship between foveal Müller cell cone disruption and multifocal electroretinogram will provide physiological evidence that the foveal Müller cell cone structure is a predictive biomarker.…”
Section: Post Hoc Studies Of Protocol T Evaluated the Effectiveness O...mentioning
confidence: 99%
“…Evaluation of higher order kernels and other approaches such as oscillatory potentials or slow double-stimulation mfERG have been used to examine the level of impairment in retinal diseases (e.g., mfERG results suggest that the inner retina is first affected in diabetic retinopathy). Alterations in mfERG might even be measurable in diabetic patients before structural changes of diabetic retinopathy occur, suggesting an opportunity to predict the disease progression (Bearse et al, 2006;Bearse & Ozawa, 2014;Han et al, 2004;Harrison et al, 2011;Kim, Song, & Yu, 2007;Laron et al, 2012;Ng, Bearse, Schneck, Barez, & Adams, 2008;Onozu & Yamamoto, 2003;Xu, Hu, Huang, Huang, & Chen, 2006;Zhu, Zhang, Wang, & Xu, 2014).…”
Section: Clinical Applicationmentioning
confidence: 99%